Social Robot Design and the Aesthetics of Imperfection - Rousi, Rebekah; Haimes, Paul (Palgrave Macmillan, 2024)
Humans are, by nature and nurture, flawed from the outset in a variety of physical and socio-psychological ways. Humans strive however, to achieve perfection within themselves and phenomena around them. Human imperfection can be seen as an impetus behind all technological development. Technology augments human abilities and compensates for limitations. From an aesthetic perspective, little has been said about the role of imperfection and its connection to spirituality in human-robot interaction. The influence that spirituality has on aesthetic experience, and particularly the perception of imperfection seems greatly neglected in contemporary human-technology discourse. In this chapter, the authors explain the potential for instrumental aesthetic imperfection through the lens of Japanese philosophy and Christianity by drawing on Kierkegaard’s three stages of life in light of human-technology interaction paradigms, practical design considerations and Wabi-Sabi.
Keywords: Christian theology; Wabi-Sabi; Japanese philosophy; Imperfection; Design; Aesthetics; Human–robot interaction; Social robots; fi=Viestintätieteet|en=Communication Studies|